К вопросу о гидрообъемной механической трансмиссии - Бибик, Д. В. (НТУ "ХПИ", 2008)
The article is devoted to reviewing a progress in creating the hydrovolumetric transmissions of radial type with ball pistons. The completeness of studying design issues of hydrovolumetric transmissions of GOP-900 type is analyzed, as well as trends of further studying are mapped out.
Keywords: бронетанковая техника; защищенность вооружения; огневая мощь; подвижность; гидропередача; шариковые поршни